2010
DOI: 10.1080/10408398.2010.499811
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biotechnology of Carotenoids

Abstract: Carotenoids are one of the most widespread groups of pigments in nature and more than 600 of these have been identified. Beside provitamin A activity, carotenoids are important as antioxidants and protective agents against various diseases. They are isoprenoids with a long polyene chain containing 3 to 15 conjugated double bonds, which determines their absorption spectrum. Cyclization at one or both ends occurs in hydrocarbon carotene, while xanthophylls are formed by the introduction of oxygen. In addition, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
139
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(146 citation statements)
references
References 297 publications
1
139
1
5
Order By: Relevance
“…This means that profile of egg yolk carotenoids may vary significantly from country to country due to variable feed utilizations as per the feed regulations and the rearing system (Hargitai et al, 2006;Namitha & Negi, 2010;Nimalaratne et al, 2013). For example, in table eggs, from hens raised under traditional commercial conditions, six carotenoids are present at the greatest concentration.…”
Section: Role Of Hen's Feed Additivesmentioning
confidence: 99%
“…This means that profile of egg yolk carotenoids may vary significantly from country to country due to variable feed utilizations as per the feed regulations and the rearing system (Hargitai et al, 2006;Namitha & Negi, 2010;Nimalaratne et al, 2013). For example, in table eggs, from hens raised under traditional commercial conditions, six carotenoids are present at the greatest concentration.…”
Section: Role Of Hen's Feed Additivesmentioning
confidence: 99%
“…It has been reported that hydroperoxides are neutralized by the cinnamon in a concentration dependant manner (BAroty et al, 2010). The low β-carotene content of unpasteurized samples observed in the present study may probably be due to oxidation, as oxidation is the major cause of carotenoid destruction during storage and processing (NAmithA & Negi, 2010).…”
Section: β-Carotenementioning
confidence: 87%
“…We do not presume that the bacteria that we have detected are indigenous to the Atacama Desert, but however, our data revealed that novel bacteria taxa could be isolated from these soils, representing promising biotechnological opportunities. There are several studies concerning the biotechnological applications of products synthesized by bacterium isolated from the Atacama Desert as antimicrobial agents, carotenoids or pigments, with many biological functions that can be exploited in the medicine, health foods, the foods industry, and cosmetic formulations [36,50]. Overall, the Fig.…”
Section: Phylogenetic Analysis Of the Bacterial Clones And Dominant Pmentioning
confidence: 99%